2013
DOI: 10.1007/s10495-013-0811-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of chondrocyte autophagy is an early response in the degenerative cartilage of the temporomandibular joint to biomechanical dental stimulation

Abstract: Autophagy is a cell protective mechanism for maintaining cellular homeostasis. The present study aimed to investigate whether autophagy is enhanced in the biomechanically induced degenerative cartilage of the temporomandibular joint (TMJ) and the potential role of mitogen-activated protein kinase kinase kinase kinase 3 (MAP4K3) and mammalian Target of rapamycin (mTOR) in this observation. To induce degenerative changes in the TMJs, rats were subjected to biomechanical dental stimulation by moving 4 molars away… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 46 publications
5
44
0
1
Order By: Relevance
“…Recent studies have demonstrated that autophagy is involved in certain bone and cartilage diseases, such as cervical disc degeneration (42), cartilage degeneration of the temporomandibular joint (23), degradation of Meckel's cartilage (43) and OA (44). However, the results regarding changes in autophagy and the specific role of autophagy in the progression of OA are sometimes contradictory (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that autophagy is involved in certain bone and cartilage diseases, such as cervical disc degeneration (42), cartilage degeneration of the temporomandibular joint (23), degradation of Meckel's cartilage (43) and OA (44). However, the results regarding changes in autophagy and the specific role of autophagy in the progression of OA are sometimes contradictory (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Aging is an important risk factor for the development of OA and is associated with the progressive accumulation of damaged macromolecules and organelles in somatic cells [27], potentially mediated by downregulation of the autophagic disposal of such damaged cellular components [28]. Autophagy-related proteins unc-51-like autophagy activating kinase 1 (ULK1), Beclin1 and microtubule-associated protein 1A/1B-light chain 3 (LC3) are reported to be expressed at high levels in healthy human cartilage [25,29,30], however, their expression decreases during OA [25,26]. Mechanistic target of rapamycin complex 1 (mTORC1) intracellular signalling pathway is an autophagic regulator that when inhibited activates the process of autophagy [31].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a rat model of biomechanically-induced degenerative cartilage of the temporomandibular joint (TMJ), some have proposed that autophagy is induced as an early event post injury, as observed by increased autophagosome detection by TEM, increased levels of beclin1 and LC3, as well as decreased mTOR and MAP4K3 activities [245]. In contrast, in bovine and human cartilage explants subjected to mechanical impact, autophagy was inhibited, and rapamycin treatment of mechanically-injured explants induced the expression of autophagy regulators and prevented cell death and glycosaminoglycans (GAG) release [246].…”
Section: Cell Death Regulators In Chondrocytesmentioning
confidence: 99%